Cisadane River: Challenges and Potential in the Context of Geography, Social Life of Individuals, Political Organizations, and Implementation of Sustainable Development Goals (SDGs) - M. Nuzul Wibawa*; Faisal Faisal (Universitas Syiah Kuala, 2023)
This study aims to; 1) Know the behavior of the people who live around the Cisadane River, 2) Know the Regulations, Operations, and Supervision of Every action taken by the surrounding community through which the Cisadane River flows, 3) Knowing the Constraints, Problems, and Challenges experienced by the government in overcoming problems that occur around existing problems and the impact of polluted environments. This research is qualitative. The method used is a normative juridical study. There are two types and sources of data: primary and secondary. In addition, a review of documents and literature materials that support research and problem analysis is also carried out. The research results show that the Cisadane River impacts individual and social life. While providing an essential source of livelihood, transportation, and recreational value, the river also carries flooding risks and environmental damage. Therefore, it is vital to manage and maintain the Cisadane River properly, as well as involve the community in efforts to conserve and protect the river’s environment in order to maintain the quality of life and the sustainability of the communities living in the vicinity, which are in line with the Implementation of the Sustainable Development Goals (SDGs).